Evaluation Method for Thixotropy of Clay Subjected to Unconfined Compressive Test - Tang, Bin; Zhou, Biaohe; Xie, Liang; Yin, Jianfeng (Frontiers in Earth Science, 2021)
Thixotropy is a hot topic in the field of rheology of dispersed systems. To study the quantitative index and evaluation method of thixotropy of clay is of great significance to evaluate the safety of foundation under long-term load. To explore the index system and classification methods of thixotropy for clay, unconfined compressive strength tests were carried out on three groups undisturbed soil and remolded soil that was cured to different times after remodeling of the Zhanjiang Formation in China, we can get the unconfined compressive strength values of the samples, and establish the relation between the unconfined compressive strength and curing time of remodeled soil. The concept of thixotropic sensitivity is introduced to reflect the relation between thixotropy and structure. According to the relation between thixotropy sensitivity and curing time and its logarithmic value, two indexes of structural recovery coefficient K and structural recovery index K_e were established to evaluate the thixotropy of structural clay in Zhanjiang Formation. Follow the method of the structural classification method of soil, the boundary values of structural recovery coefficient K_Ι and K_ΙΙ are calculated to classify the thixotropy of soil. When the value of K is less than K_Ι, the thixotropy of soil is weak.When the value of K is greater than K_Ι and less than K_ΙΙ, the thixotropy of soil is moderate.When the value of K is greater than K_ΙΙ, the thixotropy of soil is strong. The method is used to discuss the thixotropy of soil in the literature, and the rationality of the method is verified. The results show that this method can be used to preliminary classify the thixotropy of soil.